Competition to attract foreign direct investment through tax incentives as a threat for the realisation of socio-economics in Africa - Bissessur, Pramod (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.